Structure and photoluminescence of helium-intercalated fullerite C₆₀ - Legchenkova, I.V.; Prokhvatilov, A.I.; Stetsenko, Yu.E.; Strzhemechny, M.A.; Yagotintsev, K.A.; Avdeenko, A.A.; Eremenko, V.V.; Zinoviev, P.V.; Zoryansky, V.N.; Silaeva, N.B.; Ruoff, R.S. (Физика низких температур, 2002)
Intercalation of C₆₀ single crystals with helium was studied by powder x-ray diffractometry. It was established that the intercalation is a two-stage process, octahedral cavities are filled first and then tetrahedral ones, the chemical pressure being negative during both stages. For the first time low-temperature (5 K) photoluminescence spectra of helium-intercalated fullerite C₆₀ were studied. The presence of helium in lattice voids was shown to reduce that part of the luminescent intensity which is due to the emission of covalently bound pairs of C₆₀ molecules, the socalled "deep traps" with the 0-0 transition energy close to 1.69 eV. The mechanism of the effect of the intercalation with helium on the pair formation in fullerite C₆₀ is discussed.